The United States Commercial Space Launch Competitiveness Act: The Creation of Private Space Property Rights and the Omission of the Right to Freedom From Harmful Interference - Elliot Reaven (Washington University Law Review, 2016)
In March 2004, the European Space Agency successfully launched the Rosetta Spacecraft from Kourou, French Guiana. Over $1.5 billion dollars, ten years, and four billion miles later, the Rosetta Spacecraft released a sophisticated 220-pound probe called the “Philae,” which landed on Comet 67P/Churyumov-Gerasimenko on November 12, 2014. The landing on Comet 67P, the first of its kind, is one of the most recent technological advancements in space travel and exploration. During its year-long stay on Comet 67P, the Philae probe has drilled into the surface to collect samples, taken a series of photographs, and conducted a swath of experiments, all of which have provided never-before-seen data that has the potential to shed light on the origins of the universe. Perhaps more important than the information gleaned from the Philae landing is the symbolic impact of the mission. The Philae landing establishes that humans possess—or will soon possess—the technology for extensive commercial enterprises in space. Specifically, proof of our ability to land on a comet makes the idea of landing on and potentially excavating an asteroid more realistic. Asteroids, comets’ similarly-situated cousins, present potentially extraordinary incentives for mining and exploitation. There are three types of asteroids: rare “M-class” asteroids, which contain ten times as much metal as other asteroids; “S-type” or stony asteroids; and “C-type” asteroids, which contain significant amounts of hydrated clay minerals. According to some estimates, certain “platinum-rich asteroids just 500 meters across could contain more than the entire known reserves of platinum group metals.” Additionally, because asteroids have very low gravity, the fuel required for landing and exiting is greatly diminished, making the potential cost of asteroid mining more palatable. Despite the tremendous amount of rare and precious minerals contained within asteroids, asteroid mining’s most valuable purpose may be derived from something that is already abundant on earth: water. Water, extracted from hydrated clay minerals present on asteroids, can be harvested and turned into hydrogen rocket fuel, giving asteroids the potential to be deep space gas stations. Plans to mine asteroids are not entirely new, as evidenced by the formation of several companies looking to extract resources from space enterprises.
Keywords: space law; property law; commercial; private market; The United States Commercial Space Launch Competitiveness Act